Pengaruh Kesejahteraan dan Promosi terhadap Prestasi Kerja pada Personel Kepolisian Sektor Jatiasih Kota Bekasi - Michael Bntoruan (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study is motivated by the importance of improving work performance among police personnel through factors that support their motivation and productivity, particularly welfare and promotion opportunities. Adequate welfare and fair promotion systems are believed to enhance job satisfaction and ultimately influence performance outcomes. The objective of this research is to analyze the effect of welfare and promotion on the job performance of personnel at the Jatiasih Sector Police, Bekasi City. This research employs a quantitative approach with an associative method. The study involved 30 respondents, using a census sampling technique in which all members of the population were included. Data were collected through the distribution of Likert-scale questionnaires. The data were processed using SPSS version 27 and analyzed using multiple linear regression. The results indicate that both welfare and promotion have a positive and significant effect on job performance, either partially or simultaneously. Welfare contributes to improving employees’ motivation and work satisfaction, while promotion encourages better performance through recognition and career advancement opportunities. Simultaneously, these variables significantly influence personnel performance.